Ipotesi per una contestualizzazione dell’Hypnos del Prado - Graziella Becatti (Boletín del Museo del Prado, 2016)
Until the nineteenth century, the statue of Hypnos held by the Prado Museum was thought to represent the Roman god Mercury. Its provenance is unknown, although occasional sixteenthcentury documents make reference to the existence of the masterpiece within Renaissance collections of Roman antiquities. Evidence also exists that suggests the Hypnos may have been located in the imperial Palatine Palace during ancient Roman times.